Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1186/1465-9921-12-141
|View full text |Cite
|
Sign up to set email alerts
|

VIP and endothelin receptor antagonist: An effective combination against experimental pulmonary arterial hypertension

Abstract: BackgroundPulmonary Arterial Hypertension (PAH) remains a therapeutic challenge, and the search continues for more effective drugs and drug combinations. We recently reported that deletion of the vasoactive intestinal peptide (VIP) gene caused the spontaneous expression of a PH phenotype that was fully corrected by VIP. The objectives of this investigation were to answer the questions: 1) Can VIP protect against PH in other experimental models? and 2) Does combining VIP with an endothelin (ET) receptor antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 31 publications
(45 reference statements)
1
31
0
1
Order By: Relevance
“…VIP was also shown to aid in therapy of PAH [188] and a VIP de�ciency was shown to produce an in�ammatory response [187]. VIP has been shown to stimulate the production of BH4, acting through the synthesis of the enzyme GTP cyclohydrolase I, the rate limiting step in the de novo production of BH4 [189].…”
Section: Principlementioning
confidence: 99%
“…VIP was also shown to aid in therapy of PAH [188] and a VIP de�ciency was shown to produce an in�ammatory response [187]. VIP has been shown to stimulate the production of BH4, acting through the synthesis of the enzyme GTP cyclohydrolase I, the rate limiting step in the de novo production of BH4 [189].…”
Section: Principlementioning
confidence: 99%
“…This endothelial dysfunction, vasoconstrictors predominate and vascular remodeling ensues, which entails thickening of the middle muscle and the adventitia layers in arterioles (5). ET-1 appears as the most potent vasoconstrictor in the pulmonary vasculature, and the use of ET-1 inhibitors of correspondent receptors, like bosentan and intestinal vasoactive peptide to control PH has been proposed (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…En esta disfunción endotelial predominan los vasoconstrictores y ocurre una remodelación vascular, que incluye el engrosamiento de la media muscular y de la adventicia en arteriolas (5). ET-1 aparece como el vasoconstrictor más potente en las arterias pulmonares y el uso de los inhibidores de la ET-1; se ha propuesto el uso del bosentán y sus receptores, amén del péptido intestinal vasoactivo (7,8).…”
Section: Introductionunclassified
“…Vasoactive intestinal peptide (VIP) is a molecule that acts to relax the vasculature and reduce the effects of vasoconstrictors [53]. The importance of VIP in PAH was demonstrated in mutant mice models, where deletion of the VIP gene led to significant increases in right ventricular (RV) systolic pressures, vascular remodelling and inflammation [54].…”
Section: Vasoactive Factors Vasoactive Intestinal Peptidementioning
confidence: 99%
“…In these VIP knockout mice, both the vascular and right ventricular remodelling were attenuated by treatment with VIP. Further experiments in rat models with monocrotaline-induced PAH suggested that treatment with VIP may be more effective than treatment with bosentan and that combination therapy with bosentan could potentially give a greater efficacy than either VIP or bosentan therapy alone [53].…”
Section: Vasoactive Factors Vasoactive Intestinal Peptidementioning
confidence: 99%